Effect of Micronutrient Supplementation on Blood Biochemical Parameters and Immune Status of Pre-ruminant Calves - Mishra, Alok; Singh, P.; Ojha, B. K.; Verma, A. K. (Indian Journal of Animal Nutrition, 2017)
The present study was undertaken to assess the effect of micronutrients supplementation on the blood biochemical profile and immune response in pre-ruminant calves. Sixteen day old crossbred calves (body weight 24.50Â±0.56 kg) were randomly allocated to control and treatment groups comprising 8 animals in each group. Diets were similar (NRC, 2001) in both the groups but in treatment group 10 mL molasses based micronutrients supplement containing 50 mg Fe, 20 mg Mn, 20 mg Zn, 5 mg Cu, 0.15 mg I, 0.05mg Co, 0.2 mg Se, 4000 IU vitamin-A, 600 IU vitamin-D, 50 IU vitamin E, 0.5 mg ascorbic acid was provided. The mean values for PCV and albumin were higher (P<0.05) in treatment group as compared to control group, however, the values of Hb, serum glucose, total proteins (g/dL), globulin (g/dL) and A: G ratio were similar in both the groups. The concentration of serum Cu and Zn was higher (P<0.05) in treatment group than control group. Also, antibody titre was higher (P<0.01) in treatment group as compared to control group. Thus, the supplementation of molasses based micro-nutrients in pre-ruminant calves showed improvement in immune response.